2008
DOI: 10.1152/ajpendo.00258.2007
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose spironolactone reduces reactive oxygen species generation and improves insulin-stimulated glucose transport in skeletal muscle in the TG(mRen2)27 rat

Abstract: JR. Low-dose spironolactone reduces reactive oxygen species generation and improves insulin-stimulated glucose transport in skeletal muscle in the TG(mRen2)27 rat. Am J Physiol Endocrinol Metab 295: E110 -E116, 2008. First published April 29, 2008 doi:10.1152/ajpendo.00258.2007.-Renin-angiotensin-aldosterone system (RAAS) activation mediates increases in reactive oxygen species (ROS) and impaired insulin signaling. The transgenic Ren2 rat manifests increased tissue renin-angiotensin system activity, elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 37 publications
10
96
0
4
Order By: Relevance
“…For example, an aldosterone excess in patients with primary aldosteronism is related to impaired glucose homeostasis (52) as well as insulin resistance (28). Several recent publications (99,194), as well as recent data from our laboratory (102), have suggested that these detrimental effects on insulin signaling are mediated by inflammatory/ oxidative stress effects of mineralocorticoids. Indeed, in the TG(mRen2)22 rat, which manifests insulin resistance (18), in vivo MR antagonism with subpressor doses of spironolactone substantially improve ex vivo insulin stimulated increases in glucose uptake in skeletal muscle, a phenomenon that is linked to reductions in NADPH oxidase activity and attenuation of ROS in soleus muscle tissue (102).…”
Section: Mineralocorticoids and Insulin Sensitivitymentioning
confidence: 91%
See 2 more Smart Citations
“…For example, an aldosterone excess in patients with primary aldosteronism is related to impaired glucose homeostasis (52) as well as insulin resistance (28). Several recent publications (99,194), as well as recent data from our laboratory (102), have suggested that these detrimental effects on insulin signaling are mediated by inflammatory/ oxidative stress effects of mineralocorticoids. Indeed, in the TG(mRen2)22 rat, which manifests insulin resistance (18), in vivo MR antagonism with subpressor doses of spironolactone substantially improve ex vivo insulin stimulated increases in glucose uptake in skeletal muscle, a phenomenon that is linked to reductions in NADPH oxidase activity and attenuation of ROS in soleus muscle tissue (102).…”
Section: Mineralocorticoids and Insulin Sensitivitymentioning
confidence: 91%
“…Insulin and IGF-1 also regulate developmental and physiological growth and remodeling of the heart (41, 78,94,102,142,163,223,234) (Fig. 2).…”
Section: Insulin and Ang II In The Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…From an experimental standpoint, it has been demonstrated that in vivo MR antagonism results in decreased NADPH oxidase activity and oxidative stress, in concert with improved insulin-stimulated glucose uptake as well as attenuated whole-body insulin resistance in skeletal muscle in a transgenic rodent model of inappropriately active tissue RAAS. 37 Nonetheless, clinical studies have not always confirmed previous experimental and clinical observations suggesting improved insulin sensitivity through aldosterone reduction and/or MR blockade. In the EPHESUS trial, MR blockade significantly reduced hypoglycaemia by approximately 43%, which could indicate impaired glycaemic control.…”
Section: Raas Inhibition In the Clinical Settingmentioning
confidence: 97%
“…Likewise, when MCR were blocked in the Ren2 rat (a model of secondary hyperaldosteronism and insulin resistance) insulin sensitivity and insulin receptor signaling improved markedly, while NADPH oxidase activity and ROS production declined 35 . (5) release of the chaperone HSP90, traslocation of the aldo-MCR complex to the nucleus, and (6) transactivation of target genes.…”
Section: Aldosterone Mcr and Peripheral Insulin Actionmentioning
confidence: 99%